2019
DOI: 10.9734/jpri/2019/v31i630346
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Study of Students and Staff of Nursing about Euthanasia in Behbahan City, 2018

Abstract: Introduction: Nursing students are part of a clinical teaching team in the course of education. And it is important to examine their attitude toward euthanasia. Investigating the attitude of nursing students towards euthanasia has always been welcomed by researchers. These studies often indicate a lack of acceptance of euthanasia among nurses, but different percentages of opposition to euthanasia have been reported. This study aimed to determine the attitudes study of students and staff of nursing about euthan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…In the present study, males showed better acceptancy of euthanasia than females. These findings were consistent with earlier studies among health care professionals (Ay & Oz, 2019;Fatemeh et al, 2019;Rafi et al, 2019;Vakili et al, 2012). Medical students had more pro-euthanasia attitudes than nursing students.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, males showed better acceptancy of euthanasia than females. These findings were consistent with earlier studies among health care professionals (Ay & Oz, 2019;Fatemeh et al, 2019;Rafi et al, 2019;Vakili et al, 2012). Medical students had more pro-euthanasia attitudes than nursing students.…”
Section: Discussionsupporting
confidence: 93%
“…The fact that some of the nursing students were in favour of euthanasia is not surprising, considering the gradual spread of this line of thought among healthcare professionals in Spain (Crusat-Abelló and Fernández-Ortega, 2021;Rodríguez-Calvo et al, 2019;Tamayo-Velázquez et al, 2012). However, it is important to note that in this study we only found two clearly opposing positions, which may be related to a lack of reflection and training in moral deliberation (Martins et al, 2020;Ranjbar et al, 2018) about the complexity of this ethical conflict and its consequences in undergraduate education (Rafi et al, 2019).…”
Section: Discussionmentioning
confidence: 54%